2018
DOI: 10.1101/428342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elimination of peripheral auditory pathway activation does not affect motor responses from ultrasound neuromodulation

Abstract: Recent studies in a variety of animal models including rodents, monkeys, and humans suggest that transcranial focused ultrasound (tFUS) has considerable promise for noninvasively modulating neural activity with the ability to target deep brain structures. However, concerns have been raised that motor responses evoked by tFUS may be due to indirect activation of the auditory pathway rather than direct activation of motor circuits. In this study, tFUS-induced electromyography (EMG) signals were recorded and anal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
2
23
1
Order By: Relevance
“…We hypothesize that Sato et al observed a combined effect of direct USN and auditory effects but the direct effects were below the detection threshold of the in vivo optical system, which would primarily be sensitive to cortical activation in the living animal. This interpretation is consistent with in vivo studies in genetically deafened mice that demonstrate motor responses from transcranial ultrasound 42 . www.nature.com/scientificreports/ Role of pRf.…”
Section: Direct Neuromodulation In the Absence Of Auditory Confoundssupporting
confidence: 89%
“…We hypothesize that Sato et al observed a combined effect of direct USN and auditory effects but the direct effects were below the detection threshold of the in vivo optical system, which would primarily be sensitive to cortical activation in the living animal. This interpretation is consistent with in vivo studies in genetically deafened mice that demonstrate motor responses from transcranial ultrasound 42 . www.nature.com/scientificreports/ Role of pRf.…”
Section: Direct Neuromodulation In the Absence Of Auditory Confoundssupporting
confidence: 89%
“…Modulation of motor activity by FOC stimulation. Since ultrasound is known to modulate motor activities in vivo 5,6,17 , we next turned to the motor cortex to investigate the functional outcome of the FOC mediated neural modulation. The FOC was placed on the motor cortex based on stereotaxic coordinates and an electromyography (EMG) electrode was inserted subcutaneously and parallel to the triceps brachii muscle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent papers by the Shapiro group 12 and Lim group 13 argued that these responses could be a consequence of indirect auditory stimulation through the cochlear pathway. On the other hand, Tyler, Baccus, Shoham, Pauly, and their coworkers reported direct activation of neurons in brain slices 14 , isolated retina 15,16 , and deaf mice 17 , where no auditory circuitry is involved. A major challenge facing ultrasound neural modulation, which contributes to the mentioned controversies, is that delivery of transcranial ultrasound would inevitably go through the skull, and eventually reach the cochlea through bone transduction.…”
mentioning
confidence: 99%
“…One can view stimulation of auditory or vestibular organs as being an off-focus activated brain region where low frequencies will be more effective due to their larger focal volumes as demonstrated in Figure 8. Recent research has demonstrated how to avoid auditory stimulation by smoothing the sharp edges on an 80 ms CW pulse of ultrasound, thereby eliminating the auditory brainstem response without affecting motor responses in normal hearing mice (Mohammadjavadi et al, 2019).…”
Section: Relationships To In Vivo Studiesmentioning
confidence: 99%
“…The direct conversion of the envelope of the stimulus to a mechanical stimulus through radiation force could explain why pulse repetition frequencies in the audible range are chosen as being more effective. In vivo researchers should address this potential confound, such as by using deafened animals, using continuous stimuli (King et al, 2014;Ye et al, 2016), or smoothing the edges of ultrasound pulses to reduce audible frequency components (Wattiez et al, 2017;Mohammadjavadi et al, 2019). Other potential confounds to direct brain stimulation in addition to the auditory system are activation of the vestibular and somatosensory systems.…”
Section: Pattern Interference Radiation Force (Pirf) Neural Stimulatormentioning
confidence: 99%